TATA KELOLA ASET PASAR TRADISIONAL OLEH PEMERINTAHD DAERAH DI DESA TANJUNG PASIR KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN TAHUN 2020-2021 - Sihombing, Bakti Ibrani Exaudi; ', Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Traditional markets are one of the government assets that must be managed based on Minister of Home Affairs Regulation Number 19 of 2016 concerning Guidelines for Management of Regional Property. The problems found in the field are traditional market dysfunction and lack of management resulting in fatal damage to traditional market assets. The aim of this research is to analyze the principles of government asset management carried out by the Tanah Jawa District Government in managing traditional market assets in Tanjung Pasir village, Tanah Jawa District in 2020-2021. This research uses the theory of government asset governance according to Sholeh and Rochmansjah because there are seven principles, namely: clear and transparent ownership, effective asset management, use of appropriate technology, minimizing risk, community involvement, accountability, monitoring and evaluation. This research method uses a qualitative approach by obtaining data from interviews and documentation. The results of this research indicate that traditional markets have not functioned effectively. However, the Tanah Jawa sub-district government is still trying to utilize traditional market assets such as community entertainment venues, traditional party venues and voting venues to support more useful uses. Factors inhibiting the management of traditional market assets are resistance from the community and traders because the location of the traditional market is far from the meeting point of routes between villages, the traditional market area feels narrow, and access to the traditional market in and out is only available in one lane. Keywords: Governance, Government Assets, Traditional Markets